A Comparative Analysis of Embryo and Endosperm Proteome from Seeds of Jatropha curcas - Liu, H.; Liu, Y. J.; Yang, M. F.; Shen, S. H.
Jatropha curcas is an important economic plant for biodiesel, which is extracted mainly from the endosperm of its mature seeds. Despite the morphological and functional differences between the embryo and endosperm, proteomic characteristics of the two tissues are not yet known. Similar proteomic profiles were observed in the two-dimensional gel electrophoresis maps from the two tissues. There were 380 and 533 major protein spots in the embryo and endosperm, respectively. Fourteen identical spots, showing a notable change, were selected and identified by tandem mass spectrometry. Among these proteins, dihydrolipoamide acetyltransferase (spot 27)participates in tricarboxylic acid cycle, which is an amphibolic pathway. The two parts both included proteins related to stress (spots 8, 115, 118, 125, 130)and signal transduction (spots 7, 100, 108). According to the volume percentage of proteins in embryo and endosperm, the proteins in endosperm (spots 54, 61, 73)were catabolism-related enzymes and reserves to provide the nutrition for seed germination; the proteins in embryo (spots 27, 62, 122)were inclined to anabolism and utilized the nutrition from the endosperm to generate a new life.
Keywords: EMBRYO; ENDOSPERM; JATROPHA CURCAS; LIQUID CHROMATOGRAPHY/TANDEM MASS SPECTROMETRY; PROTEOME